Separating physical and biological controls on long‐term evapotranspiration fluctuations in a tropical deciduous forest subjected to monsoonal rainfall. Issue 7 (23rd July 2015) - Igarashi, Yasunori; Katul, Gabriel G.; Kumagai, Tomo'omi; Yoshifuji, Natsuko; Sato, Takanori; Tanaka, Nobuaki; Tanaka, Katsunori; Fujinami, Hatsuki; Suzuki, Masakazu; Tantasirin, Chatchai
Abstract Evapotranspiration (ET), especially in the mainland of the Indochina Peninsula, can impact and is impacted by the Asian monsoonal (AM) system, thereby prompting interest in its long‐term variability. To separate the physical and biological factors controlling ET variability in a tropical deciduous forest under the AM influence, 7 year eddy covariance and ancillary measurements were collected and analyzed. The 7 year mean rainfall (Pr) and ET along with their standard deviations were 1335 ± 256 and 977 ± 108 mm (about 73% of Pr), respectively, suggesting close coupling between these two hydrologic fluxes. However, other physical and biological drivers decouple seasonal and annual variations of ET from Pr. To explore them, a big‐leaf model complemented by perturbation analysis was employed. The big‐leaf model agreed well with the measured ET at daily to multiyear time scales, lending confidence in its ability to separate biological and physical controls on ET. Using this formulation, both first‐order and second‐order Taylor series expansions of the total ET derivatives were applied to the big‐leaf model and compared with measured changes in ET (dET). Higher‐order and joint terms in the second‐order expansion were necessary for matching measured and analyzed dET. Vapor pressure deficit (D) was the primary external physical controlling driver of ET. Leaf area index (LAI) and bulk stomatal conductance (gs) were shown to be the main significant biological drivers of the transpiration component of ET. It can be surmised that rainfall variability controls long‐term ET through physical (mainly D) and biological (mainly LAI and gs) factors in this ecosystem.